Mechanisms of thrombocytopenia in platelet-type von Willebrand disease - Loredana Bury; Alessandro Malara; Stefania Momi; Eleonora Petito; Alessandra Balduini; Paolo Gresele (Haematologica, 2019)
Platelet-type von Willebrand disease is an inherited platelet disorder characterized by thrombocytopenia with large platelets caused by gain-of-function variants in GP1BA leading to enhanced GPIbα-von Willebrand factor (vWF) interaction. GPIbα and vWF play a role in megakaryocytopoiesis, thus we aimed to investigate megakaryocyte differentiation and proplatelet-formation in platelet-type von Willebrand disease using megakaryocytes from a patient carrying the Met239Val variant and from mice carrying the Gly233Val variant. Platelet-type von Willebrand disease megakaryocytes bound vWF at an early differentiation stage and generated proplatelets with a decreased number of enlarged tips compared to control megakaryocytes. Moreover, they formed proplatelets upon contact with collagen, differently from normal megakaryocytes. Similarly, collagen triggered megakaryocytes showed defective activation of the RhoA-MLC2 axis, which prevents proplatelet formation, and increased phosphorylation of Lyn, which acts as a negative regulator of GPVI signaling, thus preventing ectopic proplatelet-formation on collagen. Consistently, human and murine bone marrow contained an increased number of extravascular platelets compared to controls. In addition, platelet survival of mutant mice was shortened compared to control mice, and the administration of desmopressin, raising circulating vWF, caused a marked drop in platelet count. Taken together, these results show for the first time that thrombocytopenia in platelet-type von Willebrand disease is due to the combination of different pathogenic mechanisms, i.e. the formation of a reduced number of platelets by megakaryocytes, the ectopic release of platelets in the bone marrow, and the increased clearance of platelet/vWF complexes.